Synthesis and enzymatic incorporation of norbornene-modified nucleoside triphosphates for Diels-Alder bioconjugation - Schoch, Juliane; Jäschke, Andres (RSC Advances, 2013)
Norbornene-modified nucleoside triphosphates were synthesised and enzymatically incorporated into DNA via primer extension and polymerase chain reaction. DNA strands containing several hundred norbornene moieties were prepared and successfully labelled utilising the inverse-electron-demand Diels-Alder reaction.
Gesehen am 15.07.2021